PENGARUH MAKANAN TRADISIONAL PADA DRAMA KOREA TERHADAP MOTIVASI BERKUNJUNG WISATAWAN INDONESIA KE KOREA SELATAN - Suci Sandi Wachyuni; Zephira Aisya Dalimarta; Fernanda Stefani; Hapsari Nindya Kinasih; Liem Christina Puspitasari; Muhammad Farrel Aldean Hermanto (Fakultas Pariwisata Universitas Pancasila, 2023)
The increasing number of South Korean cultural enthusiasts suggests that there is a globalization event in which South Korean culture enters Indonesia. One such culture is traditional food. Traditional food also increased the motivation for visiting Indonesian tourists to South Korea. The study focused on the influence of traditional South Korean food on Korean dramas. In this study, researchers examined how much influence traditional South Korean food appears in Korean dramas on the motivation for visiting Indonesian tourists to South Korea. This study was conducted on 57 valid respondents online using quantitative descriptive research methods. The results of this study found that the emergence of traditional South Korean food in Korean dramas affected the motivation for Indonesian tourists to South Korea through attractive and encouraging factors. The results of this study provide an understanding of the motivation of Indonesian tourists to visit South Korea, which is influenced by Korean dramas through the perspective of food tourism. The theoretical implication of this research is to find out that it turns out that soft selling through movies or dramas can attract tourists to try traditional food. This research can be implemented as a suggestion for developing strategies for developing traditional food in general